PENGALAMAN SPIRITUAL DALAM ILMU KALIGRAFI: KETENANGAN JIWA DALAM GORESAN HURUF - Nadia Sastia (Yayasan Haiah Nusratul Islam, 2026)
Islamic calligraphy occupies a central position in Islamic art as it represents not only visual beauty but also profound spiritual values. In modern contexts, art is often reduced to aesthetic appreciation, which can diminish its spiritual function within Islamic teachings. This study aims to examine Arabic calligraphy as an Islamic art form that serves as a medium for spiritual reflection, meditation, and remembrance of God. The focus of this research is to understand how calligraphy embodies Islamic values and contributes to inner calm and religious awareness in Muslim life. This study uses a qualitative approach through a literature review by analyzing scholarly journals, books, and academic writings related to Islamic art, calligraphy, and spirituality. The findings show that Islamic calligraphy holds a distinctive status because it is directly connected to the Qur’an as divine revelation. Beyond its aesthetic dimension, calligraphy functions as a visual form of dzikir that encourages contemplation, focus, and spiritual awareness. The process of writing calligraphy is also identified as a spiritual practice that requires patience, discipline, and sincerity, which support the development of inner tranquility and religious devotion. In conclusion, Islamic calligraphy should be understood not merely as an artistic expression, but as a spiritual activity that integrates aesthetic experience with religious consciousness, making it a meaningful medium for strengthening spiritual life in Islam.